Rekultywacja terenów poeksploatacyjnych w polskim górnictwie węgla brunatnego = Reclamation of post-exploitation terrains in polish lignite mining - Kasztelewicz, Zbigniew; Klich, Jerzy; Sypniowski, Szymon (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper shows current state of post-mining terrains' reclamation in particular lignite mines in Poland. Hitherto achievements regarding reclamation and revitalization of post-exploitation terrains were described. These terrains now serve the society as recreation places and significantly increase the attractiveness of the regions in which they are located.
Keywords: tereny pogórnicze; węgiel brunatny; rekultywacja; post-mining terrains,; reclamation; lignite